Education and Health for Inclusiveness. (Washington, D.C. : International Monetary Fund, 2021)
We discuss existing shortfalls and inequalities in the accumulation of human capital-knowledge, skills, and health. We analyze their immediate and systemic causes, and assess the scope for public intervention. The broad policy goals should be to improve: the quality, and not just the quantity, of education and health care; outcomes for disadvantaged groups; and lifelong outcomes. The means to achieve these goals, while maximizing value for money, include: focusing on results rather than just inputs; moving from piecemeal interventions to systemic reform; and adopting a 'whole-of-society' approach. Reforms must be underpinned by a robust evidence base.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet